H24

giải p.trình sau:

\(\dfrac{2}{x+1}-\dfrac{1}{x-2}=\dfrac{3x-11}{\left(x+1\right)\left(x-2\right)}\)

H24
1 tháng 4 2022 lúc 12:59

 \(đkxđ:x\ne-1;x\ne2\)

\(\Leftrightarrow\dfrac{2\left(x-2\right)}{\left(x+1\right)\left(x-2\right)}-\dfrac{1\left(x+1\right)}{\left(x-2\right)\left(x+1\right)}=\dfrac{3x-11}{\left(x+1\right)\left(x-2\right)}\\ \Leftrightarrow2x-4-x-1=3x-11\\ \Leftrightarrow2x-4-x-1-3x+11=0\\ \Leftrightarrow-2x+6=0\\ \Leftrightarrow-2x=-6\\ \Leftrightarrow x=3\)

Bình luận (0)

Các câu hỏi tương tự
LT
Xem chi tiết
LN
Xem chi tiết
LN
Xem chi tiết
HP
Xem chi tiết
LP
Xem chi tiết
NT
Xem chi tiết
NL
Xem chi tiết
M0
Xem chi tiết
LN
Xem chi tiết